2019
DOI: 10.24815/jimeka.v4i1.10805
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Leverage Dan Corporate Governance Terhadap Perencanaan Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2017

Abstract: AbstrakThis study aims to examine the effect of profitability, leverage, and corporate governance on tax planning. The independent variables used in this study are profitability, leverage, institutional ownership, managerial ownership, independent commissioners and audit committees. While the dependent variable in this study is tax planning.Tax planning in this study the measured of Cash Effective Tax Rate (CETR). The population in this study are manufacturing companies listed on Indonesian Stock Exchange (BEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
2
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 1 publication
5
13
2
10
Order By: Relevance
“…This theory does not apply to property and real estate companies listed on the IDX because investors and other stakeholders can directly observe the development of the company by seeing how many large governments projects the company has handled directly which shows that the company has selling power. The results of this test state that information asymmetry does not affect firm value which is supported by research conducted by Azari & Facrizal (2017), that information asymmetry does not affect firm value. Research conducted by Safitri et al (2021), shows that information asymmetry has no effect on firm value with a sample of 9 companies.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This theory does not apply to property and real estate companies listed on the IDX because investors and other stakeholders can directly observe the development of the company by seeing how many large governments projects the company has handled directly which shows that the company has selling power. The results of this test state that information asymmetry does not affect firm value which is supported by research conducted by Azari & Facrizal (2017), that information asymmetry does not affect firm value. Research conducted by Safitri et al (2021), shows that information asymmetry has no effect on firm value with a sample of 9 companies.…”
Section: Resultssupporting
confidence: 53%
“…Differences in research results were found by Noviadewi & Mulyani (2020), who states that information asymmetry has no negative effect on firm value. According to Azari & Facrizal (2017), information asymmetry has no significant effect on firm value. According to Safitri et al (2021), found that information asymmetry has no effect on firm value.…”
Section: Introductionmentioning
confidence: 99%
“…Mekanisme corporate governance dapat berjalan dengan baik apabila perusahaan mampu menerapkan lima prinsip corporate governance dengan kerjasama yang baik antara manajemen perusahaan, dewan direksi, para pemegang saham, dan pemangku kepentingan lainnya (Marfirah & Syam, 2016). Menurut Sutedi (2012) dalam Pratiwi et al, (2016), mekanisme corporate governance dibagi 2022.…”
Section: Mekanisme Corporate Governanceunclassified
“…Leverage mengukur sejauh mana perusahaan menggunakan hutang (Kurniasih & Ratna Sari, 2013). Perusahaan harus mengetahui besarnya tingkat risiko agar dapat meningkatkan volume kegiatan usaha dan operasi perusahaan (Marfiah & BZ, 2016). Beberapa riset sebelumnya oleh Ardianti (2020); Mahdiana & Amin (2020); Pratiwi et al (2021) menunjukkan bahwa Leverage memiliki pengaruh positif atas penghindaran pajak.…”
Section: 𝐷𝑒𝑏𝑑 π‘‘π‘œ πΈπ‘žπ‘’π‘–π‘‘π‘¦ π‘…π‘Žπ‘‘π‘–π‘œ = π‘‡π‘œπ‘‘π‘Žπ‘™ π»π‘’π‘‘π‘Žπ‘›π‘” π‘‡π‘œπ‘‘π‘Žπ‘™ πΈπ‘˜π‘’π‘–π‘‘π‘Žπ‘ unclassified